Complete IELTS. Bands 4-5., Teachers book - Brook-Hart, Guy.; Jakeman, Vanessa; Jay, David (Cambridge : Cambridge University Press, 2012)
Complete IELTS combines the very best in contemporary classroom practice with stimulating topics aimed at young adults wanting to study at university. Complete IELTS Bands 4-5 prepares students for the IELTS test at B1 (foundation level). It is designed to introduce students to the critical thinking required for IELTS and provide strategies and skills to maximise their score. The information, practice and advice contained in the course ensure that they are fully prepared for all parts of the test. The Teacher's Book contains detailed teacher's notes with advice on classroom procedure as well as extra teaching ideas and answer keys. There are also extra photocopiable materials including class activities, progress tests and vocabulary extension wordlists.
Keywords: English language -- Examinations, questions, etc; International English Language Testing System